The Role of Physical Education in the Gross Motor Development of Primary School Children - Agustina, Lia (Jurnal Pendidikan, Kesehatan dan Olahraga, 2023)
Physical education plays a very important role in early childhood development as it can improve gross motor skills through physical activity. The type of research used is a literature review study. A literature review study is a type of research that is carried out by studying books, literature, notes and various reports related to the problem to be solved. A literature review is a summary of the analysis of a body of research on a particular research problem by describing, evaluating and clarifying the knowledge that is already known in a subject area (Easterby-Smith, Thorpe, & Jackson, 2015: 13 in the journal Radiusman, 2020). Human physical development involves various aspects that are influenced by the systems and functions of the body's organs.The nervous system has a major impact on intelligence and emotional development. In the process of formal learning, primary school children make a lot of body movements and on average at this age they do not want to be restrained or still want to be free to learn through play. The conclusion of this article is that although their motor development is more organised at primary school age than in earlier years, it should be facilitated in a positive way.